Evaluation of novel derivatisation reagents for the analysis of oxysterols - William Griffiths (Biochemical and Biophysical Research Communications, 2014)
Oxysterols are oxidised forms of cholesterol that are intermediates in the synthesis of bile acids and steroid hormones. They are also ligands to nuclear and G protein-coupled receptors. Analysis of oxysterols in biological systems is challenging due to their low abundance coupled with their lack of a strong chromophore and poor ionisation characteristics in mass spectrometry (MS). We have previously used enzyme-assisted derivatisation for sterol analysis (EADSA) to identify and quantitate oxysterols in biological samples. This technique relies on tagging sterols with the Girard P reagent to introduce a charged quaternary ammonium group. Here, we have compared several modified Girard-like reagents and show that the permanent charge is vital for efficient MSn fragmentation. However, we find that the reagent can be extended to include sites for potential stable isotope labels without a loss of performance